Signal processing for radiation detectors - Nakhostin, Mohammad (Wiley, 2018)
"This book provides a clear understanding of the principles of signal processing of radiation detectors. It is designed to be a stand-alone book and no extensive pre-knowledge of electronics is assumed. To this end, the characteristics of pulses from various types of detectors are emphasized and an overview is given on the basic concepts required to understand detectors signal processing systems and pulse processing techniques. The author covers all important aspects of signal processing including energy spectroscopy, timing, position-sensing, pulse-shape discrimination and radiation intensity measurement. By reading this book, researchers, engineers, and graduate students working in disciplines such as nuclear physics and engineering, environmental and biomedical engineering, medical physics and radiological science will have the knowledge to optimize available systems or to setup their own experiments"--